A construção da autonomia no adulto jovem: uma visão contemporânea a partir da abordagem Junguiana - Campanile, Luciana Leite Ximenez (2015)
The psychological aspects of the young adult, the possible difficulties faced at that period of development and the resources used to cope with such difficulties are issues that have attracted the interest of scholars from various fields of study. Adopting the theoretical framework of Analytical Psychology, this research aimed at understanding in particular the acquisition of autonomy in young adults, taking into account the psychological universe of individuals who are at that development point, as well as aspects relating to their adaptation to the external world. A qualitative research was conducted, based on semi-structured interviews with ten participants, aged between 22 and 28 years. The findings suggest that this moment of the journey is full of fear, tension and doubts about themselves. The lack of rites of passage contributes to make these symptoms more severe, since there is no milestone to mark the parting from the adolescent universe and the entry into the adult world. Main challenges faced by these young people are related to the search for balance between the demands from the internal world and those from the outside world, between innovation and responsibility, between exploration and discipline. Achieving financial and emotional independence from parents, as well as being able to give up certain things in favor of autonomy, is probably among the greatest difficulties encountered by respondents. To overcome the obstacles involved in achieving those goals, they have used resources such as: courage, determination, pride, self-criticism and intuition. Some of the them described severe complications during that period, such as anorexia and depression, which have also served as a support for the development of greater autonomy. Main achievements include the ability to make choices, the experience of feeling free and an independent life. Nonetheless, individualism and the lack of investment on the collective aspects of life are aspects that stand out in the experience of those young adults. At the conclusion of this work, we explore the need for greater attention to the relations that contemporary young adults establish with their unconscious as well as with the world and the people around them